2014
DOI: 10.1016/j.leukres.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine in CMML: Matched-pair analyses of daily-life patients reveal modest effects on clinical course and survival

Abstract: Recent data suggest that azacitidine may be beneficial in CMML. We report on 48 CMML-patients treated with azacitidine. Overall response rates were high (70% according to IWG-criteria, including 22% complete responses). Monocyte count and cytogenetics adversely affected survival, whereas age, WHO-type, FAB-type, and spleen size did not. Matched-pair analyses revealed a trend for higher two-year-survival for azacitidine as compared to best supportive care (62% vs. 41%, p=0.067) and longer OS for azacitidine fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…Half of the treated patients were still alive after 2 years in comparison with only 16% in the conventional care regimen group (Fenaux et al, 2010). These results were recently confirmed by Pleyer et al, who showed that 62% of a group of 48 elderly patients (mean 71 years old) survived for 2 years after 5-azaC treatment (Pleyer et al, 2014).Decitabine is clinically effective for the treatment of MDS, and was shown to improve time to AML transformation or death. Indeed, patients treated with Decitabine had a greater median time to AML transformation or death (4.3 months) than patients receiving supportive care alone (Kantarjian et al, 2012).…”
mentioning
confidence: 63%
“…Half of the treated patients were still alive after 2 years in comparison with only 16% in the conventional care regimen group (Fenaux et al, 2010). These results were recently confirmed by Pleyer et al, who showed that 62% of a group of 48 elderly patients (mean 71 years old) survived for 2 years after 5-azaC treatment (Pleyer et al, 2014).Decitabine is clinically effective for the treatment of MDS, and was shown to improve time to AML transformation or death. Indeed, patients treated with Decitabine had a greater median time to AML transformation or death (4.3 months) than patients receiving supportive care alone (Kantarjian et al, 2012).…”
mentioning
confidence: 63%
“…Registry design, data collection and monitoring, as well as assessment of efficacy, safety and endpoints within the Austrian Azacitidine Registry were performed as previously described [8, 15]. …”
Section: Patients Design and Methodsmentioning
confidence: 99%
“…Median overall survival ranged between 12 and 37 months. 106,[110][111][112] AZA is licensed for nonproliferative CMML-2 in many countries; DAC is licensed in the United States only. These drugs are globally well tolerated, with myelosuppression being the major toxicity.…”
Section: Hmasmentioning
confidence: 99%